Children's activity and independence in the process of drawing - Morkytė, J. (Psichologija, 1962)
Human environment monitoring is based in part on total perception and imagination. The imagination's development is impossible without the parallel development of other mental functions. Sensing provides the basis for the development of thinking, imagination, and other characteristics of a child's development, and developed thinking, imagination, etc. have a positive impact on sensory development. For full-fledged child development, children must develop an active awareness that is a perception that involves more senses. As for thinking, memory, and other mental characteristics of the development, so special exercises must be organized for imagination training. S selecting the display material and the manner appropriate to the submitted task and changing the presentation of the development of new and existing images to add new content to the drawing time helps creative imagination. Without the imagination it is impossible to draw any worthwhile drawing, even drawing from nature. Thematic and decorative paintings have particularly great importance when the whole drawing is based on the type of character, componentization of anything beautiful picked from the environment, different decorative items. Therefore, these are the best exercises for imagination. Yet a child's undeveloped imagination has a random nature. It is impossible to talk about the special power of imagination and its "preservation" in old age. So far, a child is incapable of coming up with a purpose for the drawing or his own ideas, and his understanding and ability to put it to use is underdeveloped; he does not have sufficient skills drawing, according to the German pedagogues G. Britšas, G. Kolbas, F. Kulmanas, Ž. Augsburgas, and others. Children become creative only by observing and depicting the gradually developing world surrounding them, as repeatedly pointed out by N. K. Krupskaya. To teach children to draw in a natural way, taking into account their age and individual characteristics, you cannot leave them to spontaneous development. Such "freedom" only impedes the development of children's creativity. The training and development of children's creative forces during the drawing process must be united. Mastery of knowledge and skills increases with the development of creativity. When teaching children we are giving them knowledge of reality, feelings of understanding, and the ability to represent, which are necessary for creative activities.
Keywords: activity; imagination; drawing